Analisis Penerapan Tunneling Incentive Terhadap Tax Avoidance Dengan Transfer Pricing Sebagai Variabel Moderasi - Al Khansa Rezkiano Farah Nadya; Marita Marita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of tunneling incentives on tax avoidance with transfer pricing as a moderating variable in health sector companies listed on the Indonesia Stock Exchange for the period 2023–2024. This study uses a quantitative approach with secondary data and the Moderated Regression Analysis (MRA) method on 52 observations. The results show that tunneling incentives and transfer pricing do not significantly affect tax avoidance, and transfer pricing is unable to moderate this relationship. These findings indicate that in a strict regulatory environment, tax avoidance practices are not significantly influenced by ownership structure or transfer pricing mechanisms.